2021
DOI: 10.3390/ijms23010370
|View full text |Cite
|
Sign up to set email alerts
|

The p38 MAPK Components and Modulators as Biomarkers and Molecular Targets in Cancer

Abstract: The mitogen-activated protein kinase (MAPK) family is an important bridge in the transduction of extracellular and intracellular signals in different responses at the cellular level. Within this MAPK family, the p38 kinases can be found altered in various diseases, including cancer, where these kinases play a fundamental role, sometimes with antagonistic mechanisms of action, depending on several factors. In fact, this family has an immense number of functionalities, many of them yet to be discovered in terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
63
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 169 publications
(201 reference statements)
0
63
0
Order By: Relevance
“…Additionally, ROS are involved in the MAPK pathway, which modulates signal transduction and is associated with many biological functions, such as proliferation, survival, and apoptosis [ 37 39 ]. MAPK signalling is a double-edged pathway that can promote tumour progression and tumour cell death in vivo and in vitro [ 40 43 ]. The same phenomenon is also observed in osteosarcoma [ 44 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ROS are involved in the MAPK pathway, which modulates signal transduction and is associated with many biological functions, such as proliferation, survival, and apoptosis [ 37 39 ]. MAPK signalling is a double-edged pathway that can promote tumour progression and tumour cell death in vivo and in vitro [ 40 43 ]. The same phenomenon is also observed in osteosarcoma [ 44 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although we have demonstrated that the p38 MAPK/STAT1 pathway is inextricably linked to the protection mediated by EE pretreatment, there is still a lot of meaningful work worth exploring and completing. First, p38 has four subtypes: p38 α, p38 β, p38 γ and p38 δ [47] (Fig. 7).…”
Section: Discussionmentioning
confidence: 99%
“…MAP kinase P38 alpha (MAPKP-38α) is a member of mitogen-activated protein kinases activated by various stimuli like heat shock, oxidative stress, inflammatory cytokines, damaged DNA, etc., ( Zeyen et al, 2022 ). It regulates cellular functions like division, stress response, differentiation, survival, and immune ( García-Hernández et al, 2021 ). The activation of MAPKP-38α by reactive oxygen species (ROS) in cancer cells ultimately leads to the apoptosis of cancer cells ( Dolado et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%